2020
DOI: 10.1097/md.0000000000017985
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of media reportage of monkeypox in southern Nigeria

Abstract: Monkeypox is a zoonotic viral disease. Media campaigns are planned to create awareness about the disease. This is because mass media is often the leading source of information and mobilization during important health issues or crisis. The main objective of this study was to assess the media coverage of monkeypox outbreak in Nigeria. The study adopted a cross-sectional survey of residents in Southern Nigeria. A total of 600 respondents were sampled for this study through a multi-stage cluster random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 6 publications
4
17
1
Order By: Relevance
“…Similarly, animal and in vitro studies, using cidofovir and Brincidofovir (CMX001 or hexadecyloxypropyl-cidofovir), proved to be effective. These two drugs inhibit the viral DNA polymerase [42,46,58,71,78,[137][138][139], and the former is an acyclic nucleoside phosphate while the latter is a liquid conjugate of cidofovir [140]. The cellular cytotoxicity of TPOXX ®® in several cell lines, including human, was >50 µM, and interaction of TPOXX ®® with F13L gene product inhibits the production of extracellular viruses.…”
Section: Antiviralsmentioning
confidence: 99%
“…Similarly, animal and in vitro studies, using cidofovir and Brincidofovir (CMX001 or hexadecyloxypropyl-cidofovir), proved to be effective. These two drugs inhibit the viral DNA polymerase [42,46,58,71,78,[137][138][139], and the former is an acyclic nucleoside phosphate while the latter is a liquid conjugate of cidofovir [140]. The cellular cytotoxicity of TPOXX ®® in several cell lines, including human, was >50 µM, and interaction of TPOXX ®® with F13L gene product inhibits the production of extracellular viruses.…”
Section: Antiviralsmentioning
confidence: 99%
“…Another study done on assessment of media reportage on Monkey pox in the Nigeria demonstrated that the media campaigns were unsuccessful in raising awareness levels in the general population and it was discovered that inappropriate information, inadequate media programmes, and a lack of funding ultimately contributed to its inefficiency [10].…”
Section: Discussionmentioning
confidence: 99%
“…Monkeypox virus is transmitted through bodily fluids and close skin-to-skin contact, including through sexual activity 4 . Despite the media raising awareness of the virus, there are still no behavioral changes, and the attitude of the population remains the same 5 . This happens within the context of a declining immunity to smallpox and a rise in the incidence in the country 6 .…”
Section: Dear Editormentioning
confidence: 99%